Rising values for the end of the century (Journal of Parents and Teachers, 2025)
The article describes the current state of schools following the publication of the LOGSE, mentioning attitudes, values, and norms. Additionally, it includes the definition of value, the sources of values, the pedagogy of values, and evaluation.
Keywords: schools; LOGSE; Values; attitudes